Meilė Lukšienė on Teacher’s Personality - Urnėžienė, Emilija (Pedagogika, 2013)
The works by Meilė Lukšienė focus on various problems of education. The majority of them were connected by the issues related to the teacher‘s personality, which received a considerable attention from M. Lukšienė in her insights. The article makes an attempt to highlight the insights of Meilė Lukšienė into the teacher’s personality in the context of contemporary education. The object of the research: the teacher‘s personality. The methods of the research: 1) systemic-analytical, 2) comparative analysis. The origins of considerations regarding teacher’s personality and education quality may be observed in the diary of ten-year old M. Lukšienė, where she expressed her attitudes towards quality of learning. Analytical and critical thinking was characteristic of M. Lukšienė as early as her childhood. Referring to the teacher, she would emphasize the role of the teacher to shaping of learner’s personality, would stress the teacher’s authority, point to creativity as to a real wellspring of development of teacher’s creative powers, would discuss teacher’s relations with learners and highlight fairness and self-criticism. Being a child M. Lukšienė lived surrounded by creative environment, which had been created by her mom. M. Lukšienė determined education of her mom as creative education through experience considerably emphasizing the importance of experience nurtured by her mom. The contemporary nature and topicality of ideas revealed in the works by Meilė Lukšienė serve as basis for education strategy in the 21st century. The State Progress Strategy “Lithuania 2030” highlights the key values in the vision of Lithuania which include openness, creativity and responsibility and are value-based foundations of M. Lukšienė’s ideas. The comparative analysis showed that in the works by M. Lukšienė, in the State Progress Strategy “Lithuania 2030” and in the National Education Strategy creativity as well as creative and reflective teachers are highlighted. Cultural awareness stressed in the National Education Strategy is also discussed in M. Lukšienė’s works, where she allocates considerable attention to high cultural level, relation between an individual and culture, the importance of continuation and nurturance of national culture and that of humankind. The problems of teacher personality analyzed by M. Lukšienė for many years and ideas of strengthening of efficient education nurtured by her create preconditions for the successful, meaningful and creative becoming of the educational process. The teacher is the personality, who is firstly concerned about shaping of an individual, whereas the self- creation of a teacher becomes the core of culture. Therefore, a teacher, who is well aware of processes of personality and culture, has to strive for “the most successful interaction, which facilitates revelation of an individual and culture through the supreme values” between the two subjects.